Monograph review: Kabytov P.S., Fedorova N.A. «Professor Ivan Mikhailovich Ionenko: personality and time» (Kazan: Izdatel’stvo Kazanskogo universiteta, 2024, 224 p.) - V. A. Tyurin; M. M. Leonov (Вестник Самарского университета: История, педагогика, филология)
The review is an analysis of the second edition of the monograph by Kabytov P.S., Fedorova N.A. «Professor Ivan Mikhailovich Ionenko: personality and time». Professor I.M. Ionenko is a prominent Kazan historian, one of the founders of the study of the events of 1917 in the Volga region, a specialist in the field of agrarian history, head of the Department of History of the USSR at Kazan State University. The second edition of the monograph was prepared on an updated and expanded source base, including materials from central and regional archives, periodicals, numerous memoirs of students and colleagues, and new data about the scientist’s personality. The monograph presents a reconstruction of the main stages of the scientist’s life path. The main directions of scientific activity of I.M. Ionenko: problems of the Great Russian Revolution, agrarian history of the Volga region, history of the Great Patriotic War are analyzed. Pedagogical and administrative activities of the scientist and his family environment have been thoroughly studied.